The vaccine court 2.0 : the dark truth of America's vaccine injury compensation program - Rohde, Wayne R. (Skyhorse Publishing, 2021)
"The Vaccine Court looks at the mysterious and often unknown world of the National Vaccine Injury Compensation Program (NVICP), the only recourse for seeking compensation for those who have been injured by a vaccine"--